Teaching Listening Comprehension by Using Graphic Organizer to the Students with High Anxiety Level - Diah Astriyanti (IKIP PGRI Pontianak, 2021)
This study was conducted to increase the third-semester students’ listening comprehension in IKIP PGRI Pontianak who have high listening anxiety. The quantitative research method was used and the data were analyzed by using the one-way ANOVA in two groups of students with high listening anxiety in 10 meetings. The experiment group taught by using a Graphic Organizer before the listening session. Meanwhile, the other group was taught by using Advance Organizer in form of narrative text before the listening session. The result of the study indicates that Fo (3.609) is lower than Ft (3.419). It can be concluded that Graphic Organizer is not effective in teaching listening comprehension to students with high listening anxiety.